Dentistry – a professional contained career in healthcare. A qualitative study of Vocational Dental Practitioners' professional expectations - Eaton Kenneth A; Wilson Nairn HF; Clarke Wendy; Gallagher Jennifer E (BMC Oral Health, 2007)
Abstract Background New graduates in the UK presently spend one year in training as Vocational Dental Practitioners (VDPs) in preparation for primary dental care. There is a growing recognition that the emerging workforce has very different professional expectations to those of earlier generations, with implications for the profession, patients and the performance of health systems. The objectives of this study were to investigate why VDPs' in England and Wales perceive they chose dentistry as a professional career; how they perceive their vision has changed and the implications for their professional career plans, both short- and longterm. Methods Purposive sampling of schemes was undertaken to include urban, rural and metropolitan schemes, schemes in areas with and without dental schools and geographic coverage across England and Wales. All VDPs in these schemes were initiated to participate in this qualitative study using focus groups. A topic guide was utilised to standardise data collection. Informants' views were recorded on tape and in field notes. Data were transcribed and analysed using Framework Methodology. Results A total of 99 VDPs participated in the 10 focus groups. Their choice of dentistry as a professional career was motivated by multiple categories of influence: 'academic', 'healthcare', 'lifestyle', the influence of 'family', 'friends', 'careers advice' and 'work experience'. Consideration of the features of the 'professional job' appears to have been key to their choice of dentistry and the 'active rejection of medicine' as an alternative career. Entry into the profession was proving a challenging process for some but not all VDPs. Informants perceived that their vision had been moderated as a result of 'personal student debt', 'national workforce initiatives', 'limitations on clinical practice' and the 'cost of additional training'. Short term goals focused around 'recovery from the past' and 'preparation for the future'. Longterm goals covered the spectrum of opportunities within dentistry. Factors influencing VDPs longterm career plans fell into six main categories: professional, personal, financial, political, social and cultural. Conclusion VDPs chose dentistry because they perceived that it provides a financially lucrative, contained career in healthcare, with professional status, job security and the opportunity to work flexibly. They perceive that their vision is challenged by changes affecting education and the healthcare system. Longterm professional expectations were closely linked with their personal lives and support a vision of a favourable work/life balance.